Math, asked by Anonymous, 6 months ago


 \tt find  \: the  \: sum \:  \frac{1}{1 +  \sqrt{2} } +   \frac{1}{ \sqrt{2}   + \sqrt{3} }  +  \frac{1}{ \sqrt{3}  +  \sqrt{4} } + ..upto 99terms.
☆Need detailed solution.​

Answers

Answered by Draxillus
26

We have to

 \tt find \: the \: sum \: \frac{1}{1 + \sqrt{2} } + \frac{1}{ \sqrt{2} + \sqrt{3} } + \frac{1}{ \sqrt{3} + \sqrt{4} } + ..upto 99terms.

Writing the rth term

The rth term of the given expression could be written as  \tt \frac{1}{\sqrt{r} + \sqrt{r+1}}

Rationalising the den. of rth term :-

 \tt \frac{1}{\sqrt{r} + \sqrt{r+1}} = \frac{\sqrt{r+1} - \sqrt{r}}{(\sqrt{r} + \sqrt{r+1})(\sqrt{r+1} - \sqrt{r})} \\ \\ \\ = \frac{\sqrt{r+1} - \sqrt{r}}{{(\sqrt{r+1})}^2 - {(\sqrt{r})}^2}  \\ \\ \\ =  \frac{\sqrt{r+1} - \sqrt{r}}{(r+1) - (r)} \\ \\ \\ = \frac{\sqrt{r+1} - \sqrt{r}}{1} \\ \\  \\ = \sqrt{r+1} - \sqrt{r}

Therefore, 1st term =   \sqrt{2} - \sqrt{1}

2nd term =  \sqrt{3} - \sqrt{2}

3rd term =   \sqrt{4} - \sqrt{3}

.

.

.

.

99th term =   \sqrt{100} - \sqrt{99}

Adding all these term, we get

 \not{\sqrt{2}} - \sqrt{1} + \not{\sqrt{3}} - \not{\sqrt{2}} + \not{\sqrt{4}} - \not{\sqrt{3}} . . . . . . \not{\sqrt{99}} - \not{\sqrt{98}} + \sqrt{100} - \not{\sqrt{99}} \\ \\ \\ = \sqrt{100} - \sqrt{1} \\ \\ \\ =  10 - 1 \\ \\ \\ = 9

Hence, the sum of these terms is 9.

Similar questions